2013
DOI: 10.1021/op400268f
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Reduction of a 3,4-Dihydroisoquinoline for the Large-Scale Production of Almorexant: Hydrogenation or Transfer Hydrogenation?

Abstract: Several methods are presented for the enantioselective synthesis of the tetrahydroisoquinoline core of almorexant (ACT-078573A), a dual orexin receptor antagonist. Initial clinical supplies were secured by the Noyori Ru-catalyzed asymmetric transfer hydrogenation (Ru-Noyori ATH) of the dihydroisoquinoline precursor. Both the yield and enantioselectivity eroded upon scale-up. A broad screening exercise identified TaniaPhos as ligand for the iridium-catalyzed asymmetric hydrogenation with a dedicated catalyst pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Although the great majority of research work on ATH catalysts as tethered catalysts has focused on ketones, there have been some limited studies on C=N reduction 67. However, this field is significantly less developed and the catalyst versatility is not as extensive, even with untethered catalysts, although there are some very impressive examples, particularly of cyclic imine reductions 14,15,68–70. One very impressive recent example of C=N reductions using a tethered catalyst was reported by scientists at Merck, who found that catalyst 8 was particularly beneficial, and indeed superior to other catalysts tested, in the reduction of an imine substrate to a primary amine during the synthesis of a target drug molecule (Figure ) 71…”
Section: Ath Of Substrates Of Industrial Interestmentioning
confidence: 99%
“…Although the great majority of research work on ATH catalysts as tethered catalysts has focused on ketones, there have been some limited studies on C=N reduction 67. However, this field is significantly less developed and the catalyst versatility is not as extensive, even with untethered catalysts, although there are some very impressive examples, particularly of cyclic imine reductions 14,15,68–70. One very impressive recent example of C=N reductions using a tethered catalyst was reported by scientists at Merck, who found that catalyst 8 was particularly beneficial, and indeed superior to other catalysts tested, in the reduction of an imine substrate to a primary amine during the synthesis of a target drug molecule (Figure ) 71…”
Section: Ath Of Substrates Of Industrial Interestmentioning
confidence: 99%
“…The significance of asymmetric imine hydrogenation in the context of pharmaceutical and agricultural industries has been reviewed extensively. [1][2][3][4][5][6][7][8] To date, large scale AH processes have been predominantly developed with precious metal catalysts based primarily on iridium, [9][10][11][12] and rhodium 13 while ruthenium complexes are often used in asymmetric transfer hydrogenation (ATH) processes. 10,14,15 Imines are generally challenging substrates to reduce in a stereoselective manner.…”
Section: Introductionmentioning
confidence: 99%
“…1), almorexant, suvorexant, and their corresponding salts were synthesized by the medicinal chemistry department of Actelion Pharmaceuticals Ltd (Allschwil, Switzerland) as described in Supplemental Fig. S1, or according to published methods (Baxter et al, 2011;Mangion et al, 2012;Boss et al, 2013;Verzijl et al, 2013;Boss et al, 2015a,b). Chemical purity of all compounds was in excess of 97%.…”
Section: Introductionmentioning
confidence: 99%